1998
DOI: 10.1152/ajprenal.1998.275.6.f955
|View full text |Cite
|
Sign up to set email alerts
|

Urinary concentrating function in mice lacking EP3receptors for prostaglandin E2

Abstract: The actions of prostaglandin (PG) E2 are mediated by four distinct classes of PGE2E-prostanoid (EP) receptors (EP1through EP4). However, the in vivo functions of the individual EP receptor subtypes have not been delineated. To study the functions of one of these subtypes, the EP3 receptor, we generated EP3-deficient (−/−) mice by gene targeting. EP3 −/− animals survived in expected numbers, reproduced, and had no obvious abnormalities in their major organ systems. Because the EP3 receptor is expressed at high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 22 publications
2
56
1
Order By: Relevance
“…However, if multiple receptors mediate sensitization of sensory neurons in situ, then attempts to inhibit a single receptor to block the inflammatory actions of PGE 2 might be ineffective. Furthermore, although transgenic mice with knockouts of single EP receptor subtype have been developed (53)(54)(55)(56), the redundancy of EP receptor functions, which we have reported in the present study, could limit the value of these single receptor transgenic models of nociceptive transmission. Future studies using double knockout mice might be more appropriate in studying the mechanisms of pain and inflammation.…”
Section: Discussionmentioning
confidence: 85%
“…However, if multiple receptors mediate sensitization of sensory neurons in situ, then attempts to inhibit a single receptor to block the inflammatory actions of PGE 2 might be ineffective. Furthermore, although transgenic mice with knockouts of single EP receptor subtype have been developed (53)(54)(55)(56), the redundancy of EP receptor functions, which we have reported in the present study, could limit the value of these single receptor transgenic models of nociceptive transmission. Future studies using double knockout mice might be more appropriate in studying the mechanisms of pain and inflammation.…”
Section: Discussionmentioning
confidence: 85%
“…Because of its linkage to inhibitory G-protein (Gi) and its high levels of expression in renal medulla, the EP3 receptor was suggested as a candidate to mediate the actions of PGE 2 in opposing vasopressin-stimulated water flow (50), yet in a previous study, we found only subtle changes in urinary concentrating and diluting mechanisms in EP3-deficient mice (51). In these studies, we find that the absence of mPGES1 has no effect on urinary concentrating capacity.…”
Section: Discussionmentioning
confidence: 88%
“…The generation of mice deficient in EP 1 , EP 2 , EP 3 , and EP 4 receptors has been previously reported (11)(12)(13)(14). All mice used were at least 8 wk old and were bred and maintained in specific pathogen-free animal facilities at the University of North Carolina (Chapel Hill, NC), in accordance with the Institutional Animal Care and Use Committee guidelines.…”
Section: Micementioning
confidence: 99%